Abdominal aortic thromboembolism and subsequent pelvic limb myositis secondary to colitis and septicaemia in a 5‐day‐old Oldenburg colt. (13th January 2021) - Pezzanite, L.; Frank, C.; Koch, D.; Moss, A.; Landolt, G.
Summary: This case report describes the clinical progression of a 5‐day‐old Oldenburg colt presented for acute severe right hindlimb lameness. The foal had diarrhoea at presentation, and over the next 24 h became tachycardic and febrile with cold extremities in the hindlimbs and began to bear weight on the dorsum of both hind fetlocks. Diagnostic work‐up included physical examination, radiography, ultrasonography and clinicopathological testing. Treatment consisted of antibiotics, anti‐inflammatories, gastroprotectants, oral di‐tri‐octahedral smectite, hyperimmune plasma and isotonic crystalloid fluids for diarrhoea. Bandages and splints were applied to the hindlimbs to assist ambulation and prevent weightbearing on the dorsum of the fetlocks. The foal developed oedema of both hindlimbs, and ultrasonographic evaluation revealed gas pockets within the subcutaneous tissues. An ultrasound‐guided aspirate of the right hindlimb oedema was submitted for cytology, which revealed presumed Clostridial spores, and culture, which yielded heavy growth of Escherichia coli . Surgical fenestration of the hindlimbs was performed due to suspected Clostridial myositis. The foal continued to decline clinically and was humanely subjected to euthanasia. Post‐mortem evaluation revealed septicaemia and thromboembolism of the terminal abdominal aorta resulting in partial obstruction of blood flow to the pelvic limbs with resultant bacterial myositis ( Clostridium [suspected] and Escherichia coli [confirmed]). In summary, thrombosis is a potential sequela to coagulopathy seen in septicaemia and should be considered a differential diagnosis in neonatal foals presenting for lameness.